Implementasi Pendidikan Karakter di Pondok Pesantren Darusalam Tasikmalaya - Siti Julaeha (Tarbiatuna: Journal of Islamic Education Studies, 2022)
Islamic boarding schools are one of the oldest Islamic educational institutions in Indonesia, the role of Islamic boarding schools in shaping the character of their students always exists, as seen from the graduations produced by Islamic boarding schools, character education at the Khalaf Darussalam Islamic boarding school, Tasik and explaining the values ​​forming the character of the students and strategies implementation of character education in the Darussalam Islamic boarding school, Tasik. The results of this mini research conclude that Islamic boarding schools are educational institutions that implement character education integrally in the entire education and learning process in Islamic boarding schools. Because of that, a typical pesantren culture was formed which distinguishes it from the education system outside the pesantren. The values ​​developed by the pesantren in shaping the character of its students include five values: namely independence, sincerity, awareness, simplicity, and brotherhood based on the spirit of religion. In addition, the Islamic boarding school Khalaf Darussalam Tasik generally develops the motto made by Pondok Modern Gontor, because Darussalam Tasik is part of the Gontor Islamic Boarding School branch, namely: being in good health, knowledgeable, and free-thinking. The values ​​forming the character of the khalaf pesantren are then implemented both in the learning process, the formation of the pesantren culture, co-curricular activities, and extracurricular activities. Keywords: Islamic boarding school, implementation of character education, character values